Under the Christmas Tree: Belowground Bacterial Associations With Abies nordmanniana Across Production Systems and Plant Development - Garcia-Lemos, Adriana M.; Gobbi, Alex; Nicolaisen, Mette Haubjerg; Hansen, Lars H.; Roitsch, Thomas; Veierskov, Bjarke; Nybroe, Ole (Frontiers in Microbiology, 2020)
Abies nordmanniana is an economically important tree crop widely used for Christmas tree production. After initial growth in nurseries, seedlings are transplanted to the field. Rhizosphere bacterial communities generally impact the growth and health of the host plant. However, the dynamics of these communities during A. nordmanniana growth in nurseries, and during transplanting, has not previously been addressed. By a 16S rRNA gene amplicon sequencing approach, we characterized the composition and dynamics of bacterial communities in the rhizosphere during early plant growth in field and greenhouse nurseries, and for plants transplanted from the the greenhouse to the field. Moreover, the nitrogen cycling potential of rhizosphere bacteria across plant age was addressed in both nurseries. Overall, a rhizosphere core microbiome of A. nordmanniana, comprising 19.9% of the taxa at genus level, was maintained across plant age, nursery production systems and even during the transplantation of plants from the greenhouse to the field. The core microbiome included the bacterial genera Bradyrhizobium, Burkholderia, Flavobacterium, Pseudomonas, Rhizobium, Rhodanobacter and Sphingomonas which harbor several N-fixing and plant growth-promoting taxa. Never-the-less, both plant age and production system caused significant changes in the rhizosphere bacterial communities. Concerning community composition, the relative abundance of Rhizobiales (genera Rhizobium, Bradyrhizobium and Devosia) was higher in the rhizosphere of field-grown A. nordmanniana, while the relative abundance of Enterobacteriales and Pseudomonadales (genus Pseudomonas) was higher in the greenhouse. Analysis of community dynamics across plant age showed that in the field nursery, the most abundant bacterial orders showed more dynamic changes in their relative abundance in the rhizosphere than in the bulk soil. In the greenhouse, age-dependent dynamics even occurred but affected different taxa than for the field-grown plants. The N-cycling potential of rhizosphere bacterial communities showed an increase of the relative abundance of genes involved in nitrogen fixation and denitrification by plant age. Similarly, the relative abundance of reported nitrogen-fixing or denitrifying bacteria increased by plant age. However, different community structures seemed to lead to an increased potential for nitrogen-fixation and denitrification in the field versus greenhouse nurseries.